Marc Ferrez, un photographe témoin des mutations du Brésil - Confins (Confins)
Marc Ferrez (1843-1923) witnessed the extraordinary transformations experienced by Brazil from the mid-nineteenth century to the first quarter of the twentieth century, from slavery to the birth of cinema, via the construction of railways and the modernization of its cities, and left us a precious testimony in the form of high quality photography